Balancing Financial Stability and Housing Affordability : The Case of Canada - Matheson, Troy. (Washington, D.C. : International Monetary Fund, 2018)
Housing market imbalances are a key source of systemic risk and can adversely affect housing affordability. This paper utilizes a stylized model of the Canadian economy that includes policymakers with differing objectives-macroeconomic stability, financial stability, and housing affordability. Not surprisingly, when faced with multiple objectives, deploying more policy instruments can lead to better outcomes. The results show that macroprudential policy can be more effective than policies based on adjusting propertytransfer taxes because property-tax policy entails excessive volatility in tax rates. They also show that if property-transfer taxes are used as a policy instrument, taxes targeted at a broader-set of homebuyers can be more effective than measures targeted at a smaller subset of homebuyers, such as nonresident homebuyers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet